2013
DOI: 10.1155/2013/160320
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation betweenBiomphalaria alexandrinaSnails Susceptible and Resistant toSchistosoma mansoniInfection

Abstract: Much effort has been made to control schistosomiasis infection in Egypt. However, enduring effects from such strategies have not yet been achieved. In this study, we sought to determine the genetic variability related to the interaction between Biomphalaria alexandrina snails and Schistosoma mansoni. Using RAPD-PCR with eight (10 mers) random primers, we were able to determine the polymorphic markers that differed between snails susceptible and resistant to Schistosoma mansoni infection using five primers out … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Similarly, resistance character in B. glabrata and B. tenagophila snails is inherited in a dominant way (Richards & Merritt, 1972;Lewis et al, 2002;Rosa et al, 2005). Abdel-Hamid et al, (2006) and El-Nassery et al, (2013) found that both susceptibility and resistance in B. alexandrina are hereditary characters which are genetically controlled.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Similarly, resistance character in B. glabrata and B. tenagophila snails is inherited in a dominant way (Richards & Merritt, 1972;Lewis et al, 2002;Rosa et al, 2005). Abdel-Hamid et al, (2006) and El-Nassery et al, (2013) found that both susceptibility and resistance in B. alexandrina are hereditary characters which are genetically controlled.…”
Section: Discussionmentioning
confidence: 98%
“…Separation of resistant and susceptible isolates (F0) was achieved according to Zanotti-Magalhães, Magalhães and Carcalho (1997) and El-Nassery et al (2013). For selection of resistant isolates, snails that remained un-infected after two parasitic exposures, each by ten active freshly hatched miracidia/snail, were isolated and reared singly for self-reproduction under laboratory conditions (Eveland & Haseeb, 2011).…”
Section: Selection Of the Susceptible And Resistant Snail Stocksmentioning
confidence: 99%
See 1 more Smart Citation
“…Aquatic snails of the Biomphalaria genus are the intermediate hosts of the blood fluke Schistosoma mansoni [ 1 , 2 ], trematodes that infect 67 million people in Africa and South America [ 3 5 ]. When parasite eggs are expelled with human faeces in water, miracidia larvae hatch and actively search for its snail vector.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the resistance character in B. glabrata snails is inherited in a dominant manner ( Richards & Merritt 1972 , Lewis et al 2002) . Abdel-Hamid et al (2006) and El-Nassery et al. (2013) found that both susceptibility and resistance in B. alexandrina are hereditary characters and are genetically controlled.…”
Section: Discussionmentioning
confidence: 99%